Pengelolaan Perpustakaan Keliling di Rumah Zakat Kota Padang - Ikhsan, Muhamad; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
The purpose of this study is to describe how to process of management traveling library of Rumah Zakat Padang and describe any obstaoles the management of traveling library Rumah Zakat, Padang. This research method is descriptive. Data was collected through interviews with librarians of Rumah Zakat, Padang. after the data obtained through observation, then made ​​the key points that will include in this paper. Based discussion can be concluded that: (1) bookmobile Rumah Zakat of Padang through the planning process include; material information, funds human resource , funds, systems and equipment, (2) the constraints that will be faced by the mobile library in the rumah zakat field is human resources and budget funding, the government should support programs carried out by the charity bookmobile Rumah Zakat of Padang that educational equity to all walks of life in the desert city Keyword: bookmobile; management library